2005
DOI: 10.1063/1.1857474
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of anthracene with OH radicals: An experimental study of the kinetics between 58 and 470K

Abstract: The first direct measurement of the reaction rate constant of a polycyclic aromatic hydrocarbon in the gas phase in the temperature range 58-470 K is reported. The reaction is OH+ anthracene and the experiment has been performed in a continuous flow Cinetique de Reaction en Ecoulement Supersonique Uniforme apparatus, which had to be modified for this purpose. Pulsed laser photolysis of H(2)O(2) has been used to generate OH radicals and laser-induced fluorescence to observe the kinetic decay of the radicals and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 29 publications
5
37
0
4
Order By: Relevance
“…(3)] are higher and show evidence of "fall-off" behavior. [29] The reactions between OH radicals and butenes [15] and OH and anthracene, [14] and probably those between CH and butenes and CH and benzene (red in Table 3) are presumed to occur by association: but now the adducts are sufficiently large that the kinetics are in the high-pressure limit, even at the relatively low pressures found in a CRESU expansion. at 298 K; orange print indicates reactions that proceed by pressure-dependent association; red print indicates reactions that probably proceed by association in the high-pressure limit.…”
Section: Rate Constants For Neutral-neutral Reactions and Their Tempementioning
confidence: 98%
See 1 more Smart Citation
“…(3)] are higher and show evidence of "fall-off" behavior. [29] The reactions between OH radicals and butenes [15] and OH and anthracene, [14] and probably those between CH and butenes and CH and benzene (red in Table 3) are presumed to occur by association: but now the adducts are sufficiently large that the kinetics are in the high-pressure limit, even at the relatively low pressures found in a CRESU expansion. at 298 K; orange print indicates reactions that proceed by pressure-dependent association; red print indicates reactions that probably proceed by association in the high-pressure limit.…”
Section: Rate Constants For Neutral-neutral Reactions and Their Tempementioning
confidence: 98%
“…The reservoir can also be heated if species are being used which have low vapor pressures at room temperature. [14] Expansion through the Laval nozzle then provides cooling, albeit not, of course, to temperatures as low as those attained when the reservoir is at ambient temperature or below.…”
Section: Astrochemistry: Molecules In Spacementioning
confidence: 99%
“…47 It is suggested that the reaction could probably lead to the formation of cyclopropa [b]anthracene assuming that the mechanism proceeds by the addition of the CH radical to the π-system of the molecule followed by a H atom elimination.…”
Section: Ring Expansion Reaction Mechanismmentioning
confidence: 99%
“…Recently, low temperature kinetic studies have been extended to aromatic species: benzene 12-14 and anthracene. 15,16 The low temperature reactivity of the CN radical has been investigated for a range of small hydrocarbons. 17 The reactions of CN with larger hydrocarbon species including allene and propyne were found to have rate coefficients of ~4 × 10 -10 cm 3 molecule -1 s -1 over the 15-294 K range.…”
Section: Introductionmentioning
confidence: 99%